2021
DOI: 10.3390/ijerph18031280
|View full text |Cite
|
Sign up to set email alerts
|

Importance-Performance Analysis of Health Perception among Korean Adolescents during the COVID-19 Pandemic

Abstract: This study assessed the health perceptions of 333 Korean adolescents during the coronavirus disease (COVID-19) pandemic via an online questionnaire administered in October 2020, which queried the perceived importance and actual performance of health behaviors. The health perception scales used in the survey consists of the six dimensions of mental health, disease, physical activity, sleep, diet, and sanitary health. The data were primarily analyzed using paired sample t-test for analysis of difference and impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 17 publications
2
58
0
1
Order By: Relevance
“…This shows that social health has a positive impact on adolescents, even during the pandemic. Although many studies argued that adolescents' physical and mental health is at risk [11][12][13][14][15][16][17][18][19][20][21][22], we observed that online and in-person hybrid PE classes promote adolescents' social healthy by lowering alienation in PE and boosting school happiness and future healthy life expectancy. To ensure adolescents' social health during the COVID-19 pandemic, Kim's (2005) [30] strategies to resolve the issue of alienation in PE should be utilized.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…This shows that social health has a positive impact on adolescents, even during the pandemic. Although many studies argued that adolescents' physical and mental health is at risk [11][12][13][14][15][16][17][18][19][20][21][22], we observed that online and in-person hybrid PE classes promote adolescents' social healthy by lowering alienation in PE and boosting school happiness and future healthy life expectancy. To ensure adolescents' social health during the COVID-19 pandemic, Kim's (2005) [30] strategies to resolve the issue of alienation in PE should be utilized.…”
Section: Discussionmentioning
confidence: 50%
“…Furthermore, studies also note that adolescents have experienced a decline in their physical health. COVID-19 led to a spike in the prevalence of obesity among adolescents [16], diminished participation in physical activities [17][18], and lowered the level of physical activity involvement [19]. In addition, studies have also reported that adolescents showed a deteriorated health-related quality of life (HRQoL) [20] and poorer lifestyle habits [18,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…However, none of the factors were located in quadrant II (concentrate here) or IV (possible overkill), suggesting that there was no difference in health awareness between the two groups. In a previous study on the importance and performance of health awareness in adolescents, Lee, So, and Youn [21] demonstrated that hygiene and disease management were in quadrant I, while mental health, physical activity, sleep, and dietary habit management were in quadrants II and III, respectively. These findings support the results of the present study.…”
Section: Discussionmentioning
confidence: 96%
“…As shown by Lee et al, Mostert and Kesselring, and Bae and Hyeon [24,28,29], who reported the relationship between physical activity participation and health awareness, it is necessary to encourage physical activity during pandemics in order to promote adequate physical development and immunity in middle school students [21]. Intrinsically, various PE researchers have developed and implemented indoor activities that can be performed at home as the pandemic is likely to last for long.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation